The Role of Defense Diplomacy to Support Covid-19 Pandemic Responses Indonesia in 2019-2022 - Clarita Ayu Putri Setya; Abdul Kholib (CV. AFDIFAL MAJU BERKAH, 2023)
Implementation of vaccination in Indonesia is based on Presidential Regulation Number 99 of 2020 concerning Procurement of Vaccines and Implementation of Vaccinations which is actually intended to prevent the spread of Covid-19 during a pandemic. However, the vaccinations carried out also caused Post-Immunization Follow-up Events (AEFI). The purpose of writing is to find out the form of legal protection for the community as well as the government's responsibility for the Covid-19 Vaccine AEFI. The literature study research method uses a statutory, case and comparative approach. The research results show that the Covid-19 vaccination as a national program is a real form of legal protection for the wider community as well as realizing the safety of all citizens. The existence of a legal policy set by the government has actually accommodated the needs of the community before and after the Covid-19 pandemic conditions were established through various legal regulations and practically carried out by administering vaccines. However, during this process there were also Post-Immunization Follow-Up Events which resulted in health impacts on vaccine recipients. Therefore, the government has the responsibility not only to suppress the spread of Covid-19 but also to be responsible for the occurrence of AEFI. This responsibility is carried out through the formation and implementation of the authority of the National Commission on Child Protection and the National Committee on Child Protection and Child Protection which are spread at the central and regional levels by tracing KIPI cases as well as financing the KIPI cases that occur.